(untitled) (International Journal of Applied Research in Management and Economics, 2022)
This paper studies the situation of the blue economy in the Albanian part of the Adriatic Sea. As a country with a considerably long coastal line, it bears a lot of potential for the development of this sector, which includes tourism, fishery, maritime transport, and trade, as well as other related activities. The study focuses on tourism because it is one of the main contributors to the state budget, and to the fishery, due to its impact on tourism, gastronomy, exports, and the ecosystem. Data on these sectors during the last decade will be presented, with a special emphasis on the impact that Covid–19 pandemic had on tourism and fishery, how it shaped even afterward the way people make tourism, as well as their view on health and free time, due to its enormous economic and psychosocial impact. Another turning point in the performance of our blue economy is the actual armed conflict in Ukraine. Russian and Ukrainian tourists have increased impressively during the last years in Albania, and this aggravated situation has already begun to show its negative impact on our blue economy. The importance of this study lies in keeping up with the steps undertaken by our government towards this crucial sector of the economy, in terms of legislation, and real support with the right strategical politics undertaken and foreseen for the near future. It delivers recommendations to enhance these strategies to overcome the actual boundaries and develop further necessary reforms in favor of a sustainable blue economy.